Unusual foreign bodies in nose and throat - Mantri, Gaveshani; Patsani, Monalisa; Unnikrishnan, Jayakrishnan Menon; Behera, Subrat Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Ear, nose and throat practice presents the surgeons with an amazing variety of foreign bodies to deal with, some of them are truly unusual.They may be inert, hygrophilic or corrosive. Foreign body impaction in ear,nose and throat is among the medical-surgical emergencies of otorhinolaryngological practice. Some foreign bodies have been well documented among the objects that normally get impacted in ear,nose and throat. Here we present two unusual cases that happened to be managed in our institution. First case was of a patient who came with an unusual foreign body lodged in the nose and nasopharynx and the second case was of a migrating foreign body in throat. The main aim and objective of these case reports is to highlight on unusual foreign bodies and their management .These foreign bodies were never found to have been reported previously in our review of literature.